Sliding mode observer for estimating states and faults of linear time-delay systems with outputs subject to delays - Nguyen, Cuong M.; Tan, Chee Pin; Trinh, Hieu (Automatica (Oxford), 2021)
In this paper, we study the problem of estimating states and faults for a class of linear time-delay systems using sliding mode observers. Both the states and outputs are subject to constant delays. This is a challenging problem and has not yet been resolved in the literature. By appropriately using a system transformation and the H∞ filtering method, we propose a novel sliding mode observer scheme which can guarantee H∞ asymptotic stability of the state and fault estimation errors. A numerical example is provided to illustrate the effectiveness of the new result.